Agreement of the Discrepancy Index Obtained Using Digital and Manual Techniques—A Comparative Study - Nestor A. Burgos-Arcega; Rogelio J. Scougall-Vilchis; Adriana A. Morales-Valenzuela; Wael Hegazy-Hassan; Edith Lara-Carrillo; Víctor H. Toral-Rizo; Ulises Velázquez-Enríquez; Elias N. Salmerón-Valdés (Applied Sciences, 2022)
The discrepancy index evaluates the complexity of the initial orthodontic diagnosis. The objective is to compare whether there is a difference in the final discrepancy index score of the American Board of Orthodontics (ABO) when obtained using digital and manual techniques. Fifty-six initial orthodontic records in a digital and physical format were included (28 each) in 2022 at the Center for Research and Advanced Studies in Dentistry. For the digital measurements, iTero and TRIOS 3 intraoral scanners were used, along with Insignia software and cephalometric tracing with Dolphin Imaging software. Manual measurements were obtained in dental casts using the ruler indicated for the previously mentioned discrepancy index, in addition to conventional cephalometric tracing. Student’s t-test did not show statistically significant differences between the digital and manual techniques, with final discrepancy index scores of 24.61 (13.34) and 24.86 (14.14), respectively (p = 0.769). Cohen’s kappa index showed very good agreement between both categorical measurements (kappa value = 1.00, p = 0.001). The Bland–Altman method demonstrated a good agreement between continuous measurements obtained by both techniques with a bias of 0.2500 (superior limit of agreement =9.0092988, inferior limit of agreement = −8.5092988). Excellent agreement was observed in obtaining the discrepancy index through digital technique (Intraoral scanning and digital records) and manual technique (conventional records).